2017
DOI: 10.12659/msm.905388
|View full text |Cite
|
Sign up to set email alerts
|

P53 and Protein Phosphorylation Regulate the Oncogenic Role of Epithelial Cell Transforming 2 (ECT2)

Abstract: BackgroundGastric cancer (GC) is the second leading cause of cancer-related death worldwide, but little progress has been achieved in the treatment of advanced or metastatic GC. GC is highly heterogeneous and more studies are needed to elucidate the metastatic mechanisms. Epithelial cell transforming 2 (ECT2) has been reported to be up-regulated in GC tissues, but its signaling mechanisms remain unclear.Material/MethodsIn this study, we used Western blot analysis to compare the expression level of ECT2 in 2 GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In addition to miRNAs, several signalling molecules have been identified as up-stream regulators of ECT2 expression in cancer cells; these promote cancer progression in an ECT2-dependent manner. Chen et al [56] revealed that p53, an up-stream signalling molecule of ECT2, inhibits the ECT2-induced proliferation, invasion, and epithelial-mesenchymal transition of gastric cancer cells. Mansour et al [57] demonstrated that the E6-associated protein suppresses breast cancer invasiveness, colonisation, and metastasis in vivo via the inhibition of the ECT2-Rho signalling axis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to miRNAs, several signalling molecules have been identified as up-stream regulators of ECT2 expression in cancer cells; these promote cancer progression in an ECT2-dependent manner. Chen et al [56] revealed that p53, an up-stream signalling molecule of ECT2, inhibits the ECT2-induced proliferation, invasion, and epithelial-mesenchymal transition of gastric cancer cells. Mansour et al [57] demonstrated that the E6-associated protein suppresses breast cancer invasiveness, colonisation, and metastasis in vivo via the inhibition of the ECT2-Rho signalling axis.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were counted under a microscope from 5 random fields. The invasion assay was performed as described before [ 13 ]. In the migration assay, the chamber was pre-coated with 20 μl 0.3 mg/ml Matrigel (BD Biosciences), and the number of seeded cells was 1×10 4 cells/well instead of 3×10 3 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…While wild-type p53 inhibits the expression of Ect2, mutant p53 was found to increase Ect2, as observed in gastric cancer cells. This overexpression of Ect2 significantly promotes cancer cell proliferation, migration, and invasion [ 71 ]. Chen and colleagues also found that phosphorylation of residue Thr359 on Ect2 is essential for the oncogenic activity of Ect2.…”
Section: Rho-specific Gefs: Net1 and Ect2 In Ddrmentioning
confidence: 99%
“…Chen and colleagues also found that phosphorylation of residue Thr359 on Ect2 is essential for the oncogenic activity of Ect2. Elimination of the phosphorylation of Thr359 decreased RhoA activation and epithelial–mesenchymal transition (EMT), which resulted in the inhibition of the proliferation of malignant cancer cells [ 71 ].…”
Section: Rho-specific Gefs: Net1 and Ect2 In Ddrmentioning
confidence: 99%